El cumplimiento de los estándares de aprendizaje del área de la matemática de los niños de cuarto grado de la unidad educativa Victoria Vásconez Cuvi-Simon Bolivar-Elvira Ortega de la ciudad de Latacunga - Chicaiza de la Cruz, Fanny Yolanda (2015)
The present investigative work was aimed at “Designing Mathematics teaching strategies for the learning standards in the four-grade children”, it is an answer to the problem “How will the application of a proper mathematics teaching process allow the development of learning standards? The utilized methods for the compilation of information were: survey for students and teachers, interview for the authorities at the educative institution. The investigation of this investigation show that mathematics classes are not motivating, besides the teaching are not interesting enough, learning standards for Mathematics are applied, there is not a combination of scenarios, solutions are not searched in order to make the class more attractive, nor groups strategies. The contribution of this investigation is an active strategies guide for the improvement of the learning; the purpose is to help the teacher to improve the teaching and learning of this area.